Depopulation and importance of agriculture in Japan: Implications from the overlapping generations and general equilibrium growth accounting model - Tomoko Kinugasa; Mitoshi Yamagucki (Economics & Finance Research, 2013)
We investigate the effects of demographic change on agriculture and nonagriculture in Japan while considering capital accumulation and total population and labour. Combining the overlapping generations model with the three generations and general equilibrium growth accounting models, we simulate the effect of demographic change on agricultural and nonagricultural inputs and outputs. Our simulation analyses show that demographic change greatly influenced agriculture and nonagriculture through capital accumulation although the influences of total population and labour were not negligible. Remarkable demographic dividends like the decline of young dependents and increase of adult longevity greatly influenced capital accumulation in Japan in the 1950s to the 1990s, which decreased the importance of agriculture. In the future, aggregate capital in Japan will presumably decrease due to a decline of the working age population, which may result in the disappearance of the advantages of nonagriculture and an increase of the importance of agriculture.
Keywords: 330